The E-Marketing Mix Strategy of Tokopedia Salam during the Covid-19 Pandemic - Mishbakhudin, Muhammad; Aisyah, Muniaty (Universitas Prasetiya Mulya, 2021)
Technological developments and government plans in the sharia economic sector supported by the large potential of the Muslim market triggered the launch of sharia features in the e-commerce marketplace. This study aimed to analyze the effect of the e-marketing mix consisting of e-product, e-price, e-place, and e-promotion variables on consumer decision through e-trust in the sharia marketplace Tokopedia Salam during the Covid-19 pandemic. The sampling method used was purposive sampling with 150 respondents. The data analysis method used was Partial Least Square. The results of the study showed that there is a direct significant effect between the e-marketing mix variables, namely e-product, e-price, and e-promotion on e-trust, except for the e-place. Meanwhile, only e-promotion and e-trust variables have a significant direct effect on consumer decision. The results of this study also showed that e-product, e-price, and e-promotion indirectly have a significant effect on consumer decision through e-trust, except for the e-place. Tokopedia Salam with its various sharia characteristics is expected to provide other offers during the pandemic with things that are more familiar to marketplace customers such as basic product, competitive prices, various promotions, and free shipping.